SPEECH STYLE OF JOKO WIDODO IN INDONESIA YOUNG CHANGEMAKER SUMMIT (IYCS) SPEECH 2012 - PAMUNGKAS, FIRDAUS DITYA (Jurnal Ilmiah Mahasiswa FIB, 2014)
Keyword: Sociolinguistic, Speech, Speech Style.This study is about speech style of Joko Widodo in Indonesia Young Changemaker Summit (IYCS) 2012. There are three problems to be solved in this study: (1) What are the types of speech style used by Joko Widodo in Indonesia Young Changemaker Summit 2012; (2) what types of speech are mostly used by Joko Widodo in Indonesia Young Changemaker Summit 2012; (3) what factors influence Joko Widodo in using certain speech in Indonesia Young Changemaker Summit 2012.This study formulation uses qualitative approach to give clear understanding without any hypothesis approach. The data of this study Joko Widodo’s utterance in Indonesia Young Changemaker Summit (IYCS) speech 2012.This study reveals the type of speech style of Martin Joos theory (frozen style, formal style, consultative style, casual style, intimate style) used by Joko Widodo in Indonesia Young Changemaker Summit 2012. From the complete sentences used by Joko Widodo in his speech, it is revealed that he tends to use consultative style as the major style of his speech. He does not use frozen style and intimate style in formal conference. Age and social background of the addressee become the main factor for Joko Widodo in using consultative style.For the next study, the writer suggests that this thesis can be used as an additional reference or comparative studies about speech style which analyzes human speech or other form of utterance. The writer also suggests that the other studies about speech style should be done to improve the finding and result of the previous studies.